Frontispiece: β2, 2‐Amino Acid N‐Carboxyanhydrides Relying on Sequential Enantioselective C(4)‐Functionalization of Pyrrolidin‐2, 3‐diones and Regioselective Baeyer–Villiger Oxidation. Issue 34 (16th June 2017) - Badiola, Eider; Olaizola, Iurre; Vázquez, Ana; Vera, Silvia; Mielgo, Antonia; Palomo, Claudio
Abstract : Expanding the field : A simple metal free machinery comprised by an organocatalytic Michael reaction of pyrrolidin‐2, 3‐diones and a regioselective Baeyer–Villiger rearrangement of the resultant adducts is reported en route to β 2, 2 ‐amino acid coupled products. For more details, see the Full Paper by C. Palomo et al. onpage 8185 ff.